Super-enhancers in esophageal carcinoma: Transcriptional addictions and therapeutic strategies - Shi, Yang; Wang, Meiqi; Liu, Dan; Ullah, Saif; Ma, Xing; Yang, Huiyu; Liu, Bingrong (Frontiers in Oncology, 2022)
The tumorigenesis of esophageal carcinoma arises from transcriptional dysregulation would become exceptionally dependent on specific regulators of gene expression, which could be preferentially attributed to the larger non-coding cis-regulatory elements, i.e. super-enhancers (SEs). SEs, large genomic regulatory entity in close genomic proximity, are underpinned by control cancer cell identity. As a consequence, the transcriptional addictions driven by SEs could offer an Achilles’ heel for molecular treatments on patients of esophageal carcinoma and other types of cancer as well. Here, we summarize the recent findings about the oncogenic SEs upon which esophageal cancer cells depend, and discuss why SEs could be seen as the hallmark of cancer, how transcriptional dependencies driven by SEs, and what opportunities could be supplied based on this cancer-specific SEs.